A Review and Meta-Analysis of Occupational Titanium Dioxide Exposure and Lung Cancer Mortality. Issue 7 (July 2018) - Le, Hien Q.; Tomenson, John A.; Warheit, David B.; Fryzek, Jon P.; Golden, Ashley P.; Ellis, Elizabeth D.
Abstract : Objective: A review of studies of occupational titanium dioxide (TiO2 ) exposure was conducted, and results from the three industry-based cohort mortality studies were summarized using meta-analysis. Methods: Summary standardized mortality ratios (SSMR) and summary Cox regression coefficients from exposure–response models were derived using random effects models. Results: Results from studies of 24, 312 TiO2 production workers were combined. SSMRs for lung cancer, all causes, all cancer, and non-malignant respiratory disease were 1.10 (95% confidence interval [CI]: 0.91 to 1.32), 0.85 (95% CI: 0.81 to 0.89), 0.92 (95% CI: 0.82 to 1.03), and 0.85 (95% CI: 0.71 to 1.02), respectively. For lung cancer, the summary hazard ratio for a 1 mg/m 3 year increase in cumulative exposure was 0.999 (0.997 to 1.002). Conclusions: Consistent with other published qualitative reviews, there is no clear evidence of an association between occupational exposure to TiO2 and lung cancer.